Kerouac in ecstasy shamanic expression in the writings - Bierowski, Thomas R., 1962-; ebrary, Inc. (Jefferson, N.C. : McFarland & Co., Publishers, 2011)
"This critical text considers Jack Kerouac as writer-shaman, exploring the content and ecstatic technique of the novels and two experimental volumes that represent critical phases of his development. Author Thomas Bierowski also examines the reception of Kerouac's work"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Kerouac, Jack, -- 1922-1969 -- Criticism and interpretation; Shamanism in literature; Electronic books